Factors for healthcare utilization and effect of mutual health insurance on healthcare utilization in rural communities of South Achefer Woreda, North West, Ethiopia - Hiwot Tilahun; Desta Debalkie Atnafu; Geta Asrade; Amare Minyihun; Yihun Mulugeta Alemu (Health Economics Review, 2018)
Objective: To identify factors for healthcare utilization and to describe effect of Mutual Health Insurance on health service utilization in rural community in South Achefer, North West Ethiopia. Methods: Across-sectional study was conducted. A total of 652 households consented to participate in the study (326 insured and 326 uninsured households). Propensity score matching was used to explain possible differences in the baseline variables between enrolled and un-enrolled households. Logistic regression analysis was used to identify factors for healthcare utilization. Results: Healthcare utilization among insured households was 50.5% (95% CI: 44.8%, 56.2%). Whilst among uninsured households, healthcare utilization was 29.3% (95% CI: 24.11, 34.47). In general, the overall healthcare utilization was 39.89% (95% CI: 35.7, 43.8). The overall increase in patient-attendance given illness among insured households was 25.2% higher compared with uninsured (t = 4.94, 95% CI: 0.145, 0.359). Educated (primary and above) (AOR = 1.84; 95% CI: 1.14, 2.98), chronic patient (AOR = 1.86; 95% CI: 1.13, 3.06), first choice was health facilities at the point of illness (AOR = 6.33; 95% CI: 2.97-13.51), rich (AOR = 2.1; 95%CI: 1.29, 3.43), and insured (AOR = 2.16; 95% CI: 1.45, 3.23) were independently associated with increased healthcare utilization. Conclusion: Enrolment to mutual health insurance increases healthcare utilization. Presence of illness in the households, household earnings, educational status, first choice of treatment at point of illness, and membership to Mutual Health Insurance scheme should be targeted during escalating of healthcare utilization.
Keywords: 330; Insurance; Enrolment; Effect; Mutual; Health; Achefere; Ethiopia